Methemoglobin binding to model phospholipid membranes - Gorbenko, G.P. (Биополимеры и клетка, 2000)
The interaction of methemoglobin with model phospholipid membranes composed of phosphatidylcholine and its mixtures with phosphatidylserine or diphosphatidylglycerol has been studied. The binding isotherms have been analyzed in terms of two-dimensional lattice models of surface adsorption and incorporation of the protein into the lipid bilayer. The binding parameters including an association constant, binding stoichiometry, enthalpy and entropy contributions to free energy change have been estimated. Исследовали взаимодействие метгемоглобина с модельными фосфолипидными мембранами, состоящими из фосфатидилхолина и его смесей с фосфатидилсерином и дифосфатидилглицерином. Изотермы связывания проанализированы в рамках двухмерных решеточных моделей адсорбции на поверхности и встраивания белка в липидный бислой. Проведена оценка константы ассоциации, стехиометрии связывания, вкладов энтальтиного и энтропийного факторов в изменение свободной энергии при образовании белок-липидных комплексов. Досліджували взаємодію метгемоглобіну з модельними фосфоліпідними мембранами, сформованими з фосфатидилхоліну та його сумішей з фосфатидилсерином і діфосфатидилгліцерином. Ізотерми зв'язування проаналізовано в рамках двовимірних моделей адсорбції на поверхні та проникнення білка в ліпідний бішар. Здійснено оцінку константи асоціації, стехіометрії зв'язування, внесків ентальпійного та ентропійного факторів у змінення вільної енергії при утворенні білок-ліпідних комплексів.